Overview of Substance Use Disorders and Incarceration of African American Males - Mukku, Venkata K.; Benson, Timothy G.; Alam, Farzana; Richie, William D.; Bailey, Rahn K. (Frontiers in Psychiatry, 2012)
Incarceration affects the lives of many African American men and often leads to poverty, ill health, violence, and a decreased quality of life. There has been an unprecedented increase in incarceration among African American males since 1970. In 2009, the incarceration rate among black males was 6.7 times that of white males and 2.6 times of Hispanic males. Substance abuse in African American males leads to higher mortality rates, high rates of alcohol-related problems, more likely to be victims of crimes and HIV/AIDS. African Americans comprised only 14% of the US population but comprised 38% of the jail population. The cost of incarcerating persons involved in substance related crimes has increased considerably over the past two decades in the United States. A reduction in the incarceration rate for non-violent offences would save an estimated $17 billion per year. Substance use disorder makes the individual more prone to polysubstance use and leads to impulse control problems, selling drugs and other crimes. The high rate of incarceration in U.S. may adversely affect health care, the economy of the country and will become a burden on society. Implementation of good mental health care, treatment of addiction during and after incarceration will help to decrease the chances of reoffending. Therapeutic community programs with prison-based and specialized treatment facilities, cognitive behavioral therapy treatment for 91–180 days, and 12-step orientation with staff specialized in substance abuse can be helpful. It is essential for health care professionals to increase public awareness of substance abuse and find ways to decrease the high rates of incarceration.